발목 골절과 동반된 원위경비관절 이개 치료 시 나사 고정법과 봉합사 단추 고정법의 비교 - 김배균; 김범수; 김성태; 선형민; Baegyun Kim; Bum Soo Kim; Seong-Tae Kim; Hyung min Sun (대한족부족관절학회지, 2025)
Purpose: This study compared the treatment outcomes between fixation using screws and suture buttons for addressing distal tibiofibular syndesmosis diastasis combined with ankle fractures. Materials and Methods: A retrospective study was conducted involving 20 patients with ankle fractures treated with screws and 21 patients treated with suture buttons for distal tibiofibular syndesmosis diastasis. The postoperative clinical outcomes were assessed using the American Orthopedic Foot and Ankle Society (AOFAS) score, while the radiological outcomes were determined by measuring the tibiofibular clear space, tibiofibular overlap, and medial clear space on the pre- and post-operative radiographs. In addition, factors such as the need for internal fixation removal surgery and the incidence of internal fixation damage were investigated. Results: One-year post-surgery, the average AOFAS score showed no significant difference between the screw and suture button surgery groups. Initially, measurements of the tibiofibular clear space, tibiofibular overlap, and medial clear space did not exhibit significant differences between the two groups. On the other hand, significant differences were observed one-year post-surgery. All patients in the screw surgery group underwent screw removal surgery. Within this group, two cases of screw breakage and one case of surgical wound infection were recorded. Conclusion: When treating distal tibiofibular syndesmosis diastasis, the screw surgery group and the suture button surgery group showed similar clinical outcomes measured by AOFAS one year after surgery, but the suture button surgery group had better results in radiological evaluation and complication frequency.